TRH/TRH-R1 Receptor Signaling in the Brain Medulla as a Pathway of Vagally Mediated Gut Responses During the Cephalic Phase - Tache, Yvette; Adelson, David; Yang, Hong (Current Pharmaceutical Design, 2014)
Pavlov’s seminal findings in the early twentieth century showed that the sight, smell or taste of food in dogs with chronic esophagostomy induces a vagal-dependent gastric acid secretion. These observations established the concept of the cephalic phase of digestion. Compelling experimental evidence in rats indicates that the three amino acid peptide thyrotropin-releasing hormone (TRH) expressed in the brainstem plays a key role in the vagal stimulation of gastric function. Neurons in the dorsal motor nucleus of the vagus (DMN) expressed TRH receptor subtype (TRH-R1) and received efferent input from TRH containing fibers arising from TRH synthesizing neurons in the raphe pallidus, raphe obscurus, and the parapyramidal regions. TRH microinjected into the DMN or intracisternally excites the firing of DMN neurons and stimulates efferent activity in the gastric branch of the vagus nerve and gastric myenteric cholinergic neurons. At the functional level, this results in a vagally-mediated and atropine-sensitive stimulation of gastric epithelial and endocrine cells secreting acid, pepsin, serotonin, histamine and ghrelin, and enteric neurons leading to increased gastric motility and emptying. Importantly, the blockade of TRH or TRH-R1 in the brainstem by pretreatment into the cisterna magna or the DMN with TRH antibody or TRH-R1 oligodeoxynucleotide antisense respectively abolishes the stimulation of gastric acid induced by sham-feeding. The gastric response to TRH injected into the DMN is potentiated by serotonin and the proTRH flanking peptide, Ps4 and suppressed by a number of brainstem peptides and cytokines activated during stress or immune response and inhibiting food intake and gastric acid secretion. These convergent data strongly support a physiological involvement of TRH signaling pathway in the brainstem to stimulate vagal activity and identified TRH-TRH-R1 system as a major effector in the dorsal vagal complex to drive the vagally mediated gut response triggered by the cephalic phase.
Keywords: enteric nervous system